Experimental and theoretical study of stereochemistry for new pseurotin A3 with an unusual hetero-spirocyclic system. Issue 45 (10th November 2016) - Xu, Lan-Lan; Cao, Fei; Yang, Qin; Li, Wan; Tian, Sha-Sha; Zhu, Hua-Jie; Zhao, Yan-Yan; Yang, Xun
Abstract: A new pseurotin A3 (3 ), which was obtained from the fungus Aspergillus terreus was converted into its acetyl derivative (4 ). Optical rotation (OR), 13 C NMR, electronic circular dichroism (ECD) and vibrational circular dichroism (VCD) were measured for (+)-4 and computed for four possible isomers using quantum theory. Absolute configuration of (+)-4 was finally assigned as (5 S, 8 S, 9 R, 10 S, 11 R, 12 Z ) by comparing the predicted OR, ECD and VCD spectra to the experimental data. Therefore, the new compound3 should have the (5 S, 8 S, 9 R, 10 S, 11 R, 12 Z ) too. Graphical abstract: